Deontic Obligations in Anti-Sexual Harassment Policies in Tertiary Institutions: A Corpus-Assisted Critical Discourse Approach - Bernard Ayine; Cornelius Fuumaale Suom-Kogle; Benjamin Amoakohene; Osei Yaw Akoto (Universitas Sanata Dharma, 2025)
Sexual harassment in higher education is a pervasive issue that carries serious implications for both institutional reputation and the well-being of victims. To address this, universities have developed anti-sexual harassment policies to guide in managing such incidents. However, the language of these documents can sometimes hinder victims’ willingness to report perpetrators. This study examined the use of deontic modalities in the anti-sexual harassment policies of three major Ghanaian universities: the University of Ghana, the University of Cape Coast, and the Kwame Nkrumah University of Science and Technology. The dataset comprised three official policy documents totaling 21219 tokens and 2675 word types, which were compiled into a specialized corpus. Using LancsBox software, we categorised the modal verbs into three deontic obligations (necessity, advisability, and possibility) and analyzed them from both institutional and victim/complainant perspectives. The findings revealed the presence of 580 modal verbs across the corpus. Deontic necessity was the most prominent, accounting for 55% of occurrences, followed by possibility (33.1%) and advisability (11.9%). Within the context of deontic necessity, institutional perspectives dominated (84.6%), framing universities as the primary agents of responsibility in combating sexual harassment, while victim/complainant perspectives were less emphasized (15.4%). Possibility and advisability were used more flexibly, offering discretionary or optional courses of action, though these too were largely framed from the institutional standpoint. By demonstrating the dominance of institutional responsibility and the limited framing of victims’ agency, this study highlights how policy language shapes institutional responses and reporting behavior. These findings contribute to the understanding of how linguistic choices in legal-institutional discourse influence power relations and victim engagement.